CENTRAL ASIAN POLITICS: INTERPLAY OF GOVERNANCE, IDEOLOGY, AND EXTERNAL INFLUENCES - Dar, Zahoor Ahmad; Muntaha, Sidrat ul; Bashir, Qurat ul Ain; Bhat, Shabir Ahmad (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The primary focus of this research paper is to analyse governance models and power dynamics in Central Asia, highlighting their ideological underpinnings and influence on state organisation and regional stability. This thorough examination looks into Central Asia’s complicated and varied political terrain, explicitly emphasising the concept of statehood, the evolution and ramifications of ideological constructs, and the profoundly complex power dynamics within the region. Through meticulous analysis, the inquiry aims to illuminate the interplay among different state institutions, the influence of constitutional frameworks, and the intricate distribution of political authority that characterises the politics of Central Asia. The study also explores the degree to which external influences shape domestic politics, drawing on theoretical perspectives on authoritarian regimes and democratic transitions, historical connections after the disintegration of the USSR, and external factors such as security considerations in the Central Asian region. Moreover, the paper scrutinises the formation and impact of ideological constructs, including their role in policy-making and governance. Employing a rigorous and comprehensive analytical approach, this research endeavour seeks to enhance our understanding of Central Asia’s intricate and deeply complex political dynamics.